Teaching Method in EFL Classroom: Types and Why Techers Use It? - Anggraini, Dwinesa; Dewi, Hernalia Citra (STKIP PGRI Tulungagung, 2025)
Teaching methods are very important in teaching learning process. It's an essential thing for teachers. To provide students with a good quality of education, it's very possible for teachers to use more than one way to teach in dynamic classroom. The aim of this research is to get to know the various teaching method used by teachers and the reason why they use it. The research method used is a descriptive qualitative method. The data are taken from teachers in